Marine litter as a vector for fouling species in Iceland - Holly A. I. Solloway; Joana Micael; Sindri Gíslason (Ocean and Coastal Research)
Marine litter has become a significant environmental issue with increasing evidence of its impact on oceans and coastal areas across the planet. This study focuses on the distribution and composition of marine litter in three regions of Iceland - Southwest, Westfjords and Northeast - and on marine litter as a vector for fouling species. The results of this study show that plastic litter was the most abundant type of both fouled and nonfouled marine litter. The beach surveys showed that land-based sources, such as mismanaged waste, were the primary contributors to beach pollution. In contrast, most fouled litter, such as fishing gear, originated from sea-based sources. Over 79,000 individuals belonging to at least 92 species were found on fouled litter at the eight surveyed sites. The Southwest had the highest abundance and the most fouled litter collected. However, the Westfjords had the highest diversity and species evenness. The phyla of the fouling species found included Annelida, Arthropoda, Bryozoa, Chordata, Cnidaria and Mollusca. Cnidaria exhibited the highest fouling percentage in the Southwest and Northeast regions, whereas Annelida had the highest fouling percentage in the Westfjords. Statistically significant relationships were found between species richness and region, abundance and region, material type, and surface rugosity and thickness. These findings highlight how fouling species can be transported via marine litter and underscore the need to continue monitoring marine litter in Iceland and implement management strategies to reduce its impact on the marine and coastal environment.